Forest Context and Policies in Portugal Present and Future Challenges - Reboredo, Fernando (World Forests, 2014)
This book will unquestionably attract a very strong interest among all those working in forest research, forest management and forest products in Portugal. In a broader sense it would no doubt be of interest to anyone working in these areas in Europe and, to a lesser extent, elsewhere in the world. The readers will likely include academics, professionals and public decision-makers working in these areas, and students of forestry, landscape architecture, rural development and planning, ecology and environmental sciences.